Impact Of Strategy Type Toward The Firm Performance: The Indonesian Chemical Industry Evidence - Budi, Suprapto (2007)
The purpose of this paper is to explore the types of strategy adopted by the firms and the impact of strategy Type upon firm performance. This paper is written based on the mail-survey of 79 firms in Indonesian chemical industry. Using factor analysis, the study found four strategic factors: technology and coordination, business expansion, competency and planning, and customer focus. Based on the result of cluster analysis, the sample firms can be grouped into three strategy typology: prospectors (23 firms), defender (34 firms) and reactor (22Jirms). Results from One Why ANOVA Analysis indicated that ROA and Sales Growth are significantly different among strategy types. Moreover, Prospectors and defenders perform equally and significantIy out perform reactors.